Tax audits as a path to tax compliance in Portugal - Araújo Marques, Joao (European journal on criminal policy and research, 2020)
Responsive regulation has a special role within compliance. It has been implemented by tax authorities through the adoption of regulatory pyramids that cover the general relationship between the tax authorities and taxpayers. Here, the effects of both the Kirchler slippery slope framework and the Braithwaitian compliance pyramid are explored to design an alternative strategy to maximise the likelihood of restitution by the offender during a tax investigation. This will result in a ‘diamond’ representation that extends the Australian Taxation Office (ATO) compliance pyramid approach, which is supported by Braithwaite. The Portuguese legal framework for tax inspections sets cooperation as a key element in the relationship between tax inspector and taxpayer, suggesting that it is consistent within a regulatory context. However, tax inspectors are still strongly viewed as a coercive authority and not as a partner in a collaborative interaction. Our practitioner model shows the different dynamics that are predicted for a tax investigation, starting from the tax inspector’s perception of the taxpayer’s motivational postures at different points of the tax investigation until a responsive regulation approach increases the hypothesis of redressment. We conclude that responsive regulation in a tax investigation context is best described by a ‘diamond’ representation to clearly show the different roles of the tax inspector, as an advisor or as an investigator. We suggest that the tax investigation diamond could be adopted as a regulatory strategy once it predicts a better chance of reaching a positive outcome of compliance/redressment in comparison with a negative outcome of persecution. This model is proposed as a theoretical starting point from which to construct experimental models that could be used as training tools for tax inspectors.